The Role of Indonesian Rural Skills Development in Empowering Organic Farming Communities - Anisah, Nairatul; Muniruddin, Muniruddin (Journal La Sociale, 2024)
The purpose of this research is to find out how Indonesian Rural Skills Development helps organic farming communities in Kebun Kelapa Village, Secanggang District, Langkat Regency become more empowered. Descriptive and qualitative examination methods used in this exploration were used. Observation, question and answer, and documentation are techniques used in this exploration in order to obtain data. The validity of information in this examination uses triangulation of information that utilizes information inquiry, precisely data reduction (data reduction), data presentation (data display), conclusion drawing (conclusion drawing). Where this method helps in examining the problems that occur in the role of rural skills development in empowering farming communities. That way researchers can find out the role of the Indonesian Rural Skills Development in empowering organic farming communities, namely as a facilitator and dynamizer by conducting training and coaching and building a wider network in empowerment. And organic farming management makes farmers know and be able to make compost and plant it organically. The benefits felt by farmer groups are in terms of economy, health, and the environment as well as the community as a whole and maximize the use of natural resources and human resources.